Sealing ability of castor oil polymer as a rootend filling material - De Martins, Giovana Ribeiro [UNESP]; Talge Carvalho, Claudio Antonio [UNESP]; Valera, Marcia Carneiro [UNESP]; De Oliveira, Luciane Dias [UNESP]; Buso, Leonardo [UNESP]; Carvalho, Alessandra Sverberi [UNESP] (FapUNIFESP (SciELO), 2009)
objective: The purpose of this study was to evaluate the sealing ability of castor oil polymer (COP), mineral trioxide aggregate (MTA) and glass ionomer cement (GIC) as root-end filling materials. Forty-five single-rooted human teeth were cleaned and prepared using a step-back technique. The apical third of each root was resected perpendicularly to the long axis direction. All teeth were obturated with gutta-percha and an endodontic sealer. After, a root-end cavity with 1.25-mm depth was prepared using a diamond bur. The specimens were randomly divided into three experimental groups (n=15), according to the root-end filling material used: G1) COP; G2) MTA; G3) GIC. The external surfaces of the specimens were covered with epoxy adhesive, except the root-end filling. The teeth were immersed in rhodamine B dye for 24 hours. Then, the roots were sectioned longitudinally and the linear dye penetration at the dentin/material interface was determined using a stereomicroscope. ANOVA and Tukey's tests were used to compare the three groups. The G1 group (COP) presented smaller dye penetration, statistically different than the G2 (MTA) and G3 (GIC) groups (p<0.05). No statistically significant difference in microleakage was observed between G2 and G3 groups (p>0.05). The results of this study indicate that the COP presented efficient sealing ability when used as a root-end filling material showing results significantly better than MTA and GIC.
Keywords: Castor oil polymer; Marginal sealing; Microleakage; Root-end filling material